Potensi Gerakan Anti Food Waste dalam Penguatan Perekonomian UMKM - Yuliana, Lingga (Efektor, 2022)
The aim of this study is to identify the role of Anti Food Waste Movement in strengthening the MSME economy with Indonesia's surplus as a case study. Descriptive qualitative method were utilized in this research with secondary data. Participants of this study are Non-Profit Organization activists who also contribute to campaigns to stop environmental damage. The result of this study demonstrated that Surplus Indonesia's presence is able to strengthen the MSME economy by cooperating in the form of partner and acting as a marketer for products that are not currently in stock. Additionally, it offers a compromise that benefits both consumers and producers. Surplus Indonesia, a supplier, distributes unsold inventory and makes a profit by marketing it. From the consumer's perspective, prices will decrease